Laboratory tests of blade radius variation on vertical shaft savonius turbine performance - Kurniawan Kurniawan; Tri Pratomo; Nurhaidah Nurhaidah; Devi Andriani; Supandi Supandi (Universitas Muhammadiyah Metro, 2023)
Wind turbines are one of the machines that are currently still used to convert wind kinetic energy so that they can be used by humans such as to drive pumps in agriculture and produce electrical energy. Savonius turbine is a vertical axis turbine that is currently widely used as an electrical energy generator, this wind turbine is a type of drag type wind turbine that has a simple design that is in the form of a semicircular curved blade side. Therefore, the author is interested in researching the resulting performance including turbine rotational speed, power generated, and wind turbine efficiency against the variation of the blade radius. The method used is experimental, the stages of this research are in the form of literature studies, making savonius turbines, testing savonius turbines with variations in blade radius as well as data retrieval, data processing, and analysis. Based on the data obtained, the rotating speed of the turbine is influenced by variations in the radius of the blade. The larger the blade radius, the smaller the turbine rotational speed. The maximum turbine rotation speed at blade radius 63 is 173 rpm, while at blade radius, 88 is 118 rpm and at blade radius 113 is 115 rpm. So the highest turbine rotating speed at a radius of 63.